Schiff Base As A Corrosion Inhibitor - Abu Hassan, Nur Hasniza; Mohd Zulkamal Punnia, Nur Natasha; Dzulkifli, Nur Nadia (2020)
Mild steel metal plays an important role as a construction material in many industries due to its low cost and excellent mechanical properties. However, acid solution that is widely used for pickling, descaling and oil-well cleaning contributes to severe corrosion problems, mostly in maintenance cost. Schiff base as a corrosion inhibitor is used to reduce the corrosion rate of the metal in this acidic medium. A thiosemicarbazone ligand, DiMMATSC acts as a corrosion inhibitor due to the presence of nitrogen and oxygen as electronegative atoms, where the interactions form a protective layer on the metal surface and block the active corrosion sites. Different concentrations of the inhibitor at 1, 2, 3, 4, and 5 mM were studied at room temperature in 1M HCl. The results showed that as the inhibitor concentration increased, the corrosion rate decreased but the inhibition efficiency increased. Langmuir isotherm was implemented to determine the type of interaction and adsorption between DiMMATSC as an inhibitor with the mild steel surface. A strong correlation from the Langmuir isotherm graph recommends that the adsorbed inhibitors occupy only one site and there are no interactions between the adsorbed species. The value of standard free energy (ΔG) from the calculation is -17.96 kJ mol -1, which indicates spontaneous physisorption of inhibitors onto the mild steel surface by forming a protective film through electrostatic interaction between charged metal surface and charged inhibitor molecules.